Dampak Perbandingan Sosial di Instagram Terhadap Fomo dan Social Anxiety di Era Digital: Sebuah Kajian Deskriptif pada Mahasiswa - Widirahayu, Margareth Dyah Anggraini; Husna, Juniana (Yayasan Tri Edukasi Ilmiah, 2024)
In the digital age, Instagram has emerged as one of the most popular social media platforms among college students. The rise of the social comparison phenomena, in which users compare their lives to those of others, often has a significant impact on mental health. The aim of this study is to investigate how social comparison on Instagram affects college students' Fear of Missing Out (FOMO) and social anxiety. Using a qualitative descriptive research method, this study involved interviews with 10 active college students aged 18 to 22 who use Instagram. The findings reveled that the majority of respondents had a positive and reflective attitude towards their lives, indicating that they were able to properly manage their usage of Instagram. However, there is a tendency of using this platform as a social comparison tool, which can cause feelings of FOMO or dissatisfaction. Furthermore, while social media continues to have a psychological impact on feelings of imperfection, it has no significant effect on real-life societal behavior. This study could help academics, educators, and mental health practitioners understand the impact of social media interactions on mental health and behavior. Understanding these dynamics allows for more effective approaches to help young people regulate their social media use while reducing the negative consequences of excessive interaction with social media sites such as Instagram.